Nordic influence on Saami folk belief: the "Buttercat" (Smörkatt) - Tatár, Magdalena (Scripta Instituti Donneriani Aboensis, 1987)
The topic of this paper is a Saami superstitious belief, namely the smørkatt "buttercat", which is without doubt a Nordic loan in Saami tradition. In olden days there were people who sold themselves or half of their souls to the devil for a considerable sum of money. They made a "butter cat" in order to get more milk. The "butter cat" looked like a ball of yarn. It stole cream and butter from the neighbour. The neighbour could not understand what had become of his butter. But he soon discovered that people who had only a few cows had a lot of butter. He chased after the "butter cat" and if he could capture it, the person who had sold his soul to the devil would die. This tradition existed among both the mountain Saamis and the Saamis who had settled down in the villages, but it was unknown among Norwegian people. The form and function of the "smørkatt" together with the way in which it could be disabled is in line with the Nordic tradition. This milk-stealing creature, which might be a hare or any other animal, is often a cat, particularly in northern Norway. It is a common Nordic tradition, too, that the animal is identical with its master, and because of that the master must die when the animal is killed. This link between the master and the animal is closer in northern Norway than anywhere else. Woman, animal and devil are linked to each other in the Nordic tradition, too, but the tradition that the master sells his soul to the devil is found only in Karasjok. It is clear, however, that people must pay for the devil’s assistance. This theme is well-known in Europe in other connections.